Comparative Genomics and Environmental Distribution of Large dsDNA Viruses in the Family Asfarviridae - Karki, Sangita; Moniruzzaman, Mohammad; Aylward, Frank O. (Frontiers in Microbiology, 2021)
The Asfarviridae is a family of Nucleo-Cytoplasmic Large DNA Viruses (NCLDV) of which African swine fever virus (ASFV) is the well-characterized. Recently the discovery of several Asfarviridae members other than ASFV has suggested that this family represents a diverse and cosmopolitan group of viruses, but the genomics and distribution of this family have not been studied in detail. To this end we analyzed five complete genomes and 35 metagenome-assembled genomes (MAGs) of viruses from this family to shed light on their evolutionary relationships and environmental distribution. The Asfarvirus MAGs derive from diverse marine, freshwater, and terrestrial habitats, underscoring the broad environmental distribution of this family. We present phylogenetic analyses using conserved marker genes and whole-genome comparison of pairwise average amino acid identity values, revealing a high level of genomic divergence across disparate Asfarviruses. Further, we found that Asfarviridae genomes encode genes with diverse predicted metabolic roles and detectable sequence homology to proteins in bacteria, archaea, and different eukaryotes, highlighting the genomic chimerism that is a salient feature of NCLDV. Our read mapping from Tara oceans metagenomic data also revealed that three Asfarviridae MAGs were present in multiple marine samples, indicating that they are widespread in the ocean. In one of these MAGs we identified four marker genes with >95% amino acid identity to genes sequenced from a virus that infects the dinoflagellate Heterocapsa circularisquama (HcDNAV). This suggests a potential host for this MAG, which would thereby represent a near-complete genome of a dinoflagellate-infecting giant virus. Together, these results show that Asfarviridae are ubiquitous, comprise similar sequence divergence as other NCLDV families, and include several members that are widespread in the ocean and potentially infect ecologically important protists.